Himalayan fruits and berries bioactive compounds, uses and nutraceutical potential - Belwal, Tarun; Bhatt, Indra D.; Devkota, Hari Prasad (Academic Press, 2023)
Himalayan Fruits and Berries: Bioactive Compounds, Uses and Nutraceutical Potential presents nutraceutical fruits and berries from the Himalayan region and highlights their potential use in nutraceutical products. Beginning with the introduction of the Himalayan region and its wild fruits, this book explores various kinds of wild fruits and berries. It includes coverage of traditional, ethnomedicinal, and local uses of potential nutraceutical fruits and analyzes their distribution, availability, and cultivation methods. The book also provides a detailed summary of clinical studies and presents "from field to industry" case studies. Wild fruits and berries play an important role in mitigating hunger in the developing world, and these fruits are consumed either in whole or extracted for use in nutraceutical production.